Under seize: neurocysticercosis in an immigrant woman and review of a growing neglected disease. (18th December 2015) - Bock, Meredith; Garcia, Hector H; Chin-Hong, Peter; Baxi, Sanjiv M
Abstract : Neurocysticercosis (NCC) is a significantly neglected tropical disease and, with increasing globalisation, a notable emerging infection in the developed world. We describe a case of ventricular NCC in a 22-year-old Mexican-American woman with a history of seizures, who presented with 2 weeks of headaches and intermittent fevers progressing to altered mental status and vomiting. Initial imaging revealed a cystic mass at the posteroinferior aspect of the third ventricle superior to the aqueduct of Sylvius, calcifications scattered throughout the parenchyma, and enlargement of the lateral and third ventricles. Initial laboratories were unrevealing and serum investigations for Taenia solium antibody were negative, but T. solium antibody was subsequently returned positive from cerebrospinal fluid. This case highlights important issues regarding the clinical presentation, diagnostic evaluation and treatment of NCC relevant to providers not only in areas with endemic disease but, importantly, in locales with diverse immigrant populations.